RESOLVING SYSTEMS OF NONLINEAR INTEGRAL EQUATIONS VIA C-CLASS FUNCTIONS - Paunović, Ljiljana (Bulletin of Natural Sciences Research, 2017)
Fixed point theorems for monotone operators in ordered metric spaces are widely investigated and have found various applications in differential and integral equations (Nieto & Rodríguez-Lόpez, 2005), (Nieto & Rodríguez-Lόpez, 2007), (Wu, 2008). Motivated by the work in (Agarwal et al., 2012) and (Luong & Thuan, 2011) we study the existence of solutions for a system of nonlinear integral equations in ordered b-metric spaces using the results given in this paper.
Keywords: b-metric spaces; compatible mappings; P-increasing; integral equation; C-class functions